Integrasi Kerangka ADDIE dalam Pembelajaran Matematika: Tinjauan PRISMA terhadap Tren Global Pengembangan Perangkat Ajar - Kristiawan, Yusie; Siswanto, Deny Hadi; Yuliawati, Yuyun (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
Education plays a crucial role in developing high-quality human resources, particularly in mathematics learning, which is often perceived as challenging due to its abstract concepts and demanding cognitive processes. Developing relevant and open-source instructional tools has become a key strategy for improving learning quality and supporting equitable access to educational resources. This article examines the application of the ADDIE model Analysis, Design, Development, Implementation, and Evaluation in the development of mathematics teaching tools. The model provides a systematic, iterative, and adaptable framework that enables educators and researchers to design contextual, interactive, and student-centered learning materials.This study employed the PRISMA framework to conduct a systematic review of 32 articles published between 2014 and 2024. The review focused on publication distribution, implementation characteristics of the ADDIE model across various educational contexts, and global trends in teaching tool development. Findings indicate that the ADDIE model is widely implemented and consistently adapted to local needs. In developed countries, integration of digital technologies, multimedia resources, and learning analytics is prominent, whereas in developing countries, the model tends to be applied with minimal-resource strategies while maintaining pedagogical effectiveness. Overall, the ADDIE model has demonstrated positive impacts on student learning outcomes, including improved conceptual understanding, engagement, and problem-solving abilities. Nevertheless, challenges such as limited time, institutional support, and resource availability continue to impede optimal implementation. The study recommends enhancing the ADDIE model to support learning innovations that prioritize student needs and align with broader educational demands, including strengthening the linkage between vocational schools and the labor market.